Статистичні звіти Одеського Піклувального комітету про в’язниці, як історичне Джерело - Юраш, Є. (Чорноморська минувшина, 2020)
У статті проаналізовано статистичні звіти Піклувального комітету про в’язниці. Визначено, що Піклувальний комітет про в’язниці був одним із важливих форм реалізації соціальної політики щодо захисту окремих груп населення. На прикладі щорічних статистичних звітів досліджено основні напрямки діяльності Одеського Піклувального комітету про в’язниці. Охарактеризовано економічну складову як одну із важливих форм його роботи. Встановлено зміну чисельного складу Одеського Піклувального комітету про в’язниці в перші роки його існування. Досліджено роботу комітету в духовному вихованні арештантів. The article analyzes "statistical reports" as a historical source for studying the history of the functioning of the Trustee Committee for Prison. The Trustee Committee for Prison has been identified as an important form of social policy for the protection of certain groups. The main directions of activity of the Odessa Trustee Committee for Prison are investigated on the example of annual statistical reports. The economic component is described as one of the important forms of work of the Committee. It was found that the source of funding for the Committee was both public funds and charitable contributions. The dynamics of the number of the members of the Odessa Trustee Committee for Prison in the first period of its existence has been established, as the annual reports indicated the list of names of all them. Statistics on the number of prisoners were analyzed and the types of crimes committed were identified. The spiritual life of prisoners is studied as an aspect of moral correction of convicts.